Natamycin Cyclodextrin Supramolecular Complex Loaded Dissolvable Lenses for the Effective Management of Fungal Keratitis - Mabel Mascarenhas; Pinal Chaudhari; Lakshmi Sruthi Mallela; Sanhita Roy; Sumit Birangal; Vivek Ghate; Ananthamurthy Koteshwara; Jesil Aranjani; Arun K. Kodoth; Shaila A. Lewis (Journal of Pharmaceutical Innovation, 2025)

Microneedle-Mediated Delivery of Amikacin-Liposomes: A Minimally Invasive Strategy against Bacterial Septicemia - Amala Maxwell; Suman Pahal; Pinal Chaudhari; Bhim Bahadur Chaudhari; Sameera Peri; Sudheer Moorkoth; Vivek Ghate; Praveen Kumar Vemula; Shaila Lewis (Journal of Pharmaceutical Innovation, 2025)

Cyclosporine a Eluting Nano Drug Reservoir Film for the Management of Dry Eye Disease - Pinal Chaudhari; Vivek M. Ghate; Madhavan Nampoothiri; Shaila A. Lewis (AAPS PharmSciTech, 2025)
Cyclosporine A (CsA) is widely used to treat dry eye disease (DED), and ocular morbidity is on the rise and is a growing concern globally. However, several drug and formulation challenges, such as poor drug solubility, short pre-corneal residence time, and poor patient compliance, have limited the ocular bioavailability of CsA to in vitro drug release, ex vivo corneal permeation, and in vivo precorneal retention. Preclinical efficacy studies were performed to assess the efficacy of CsA-complex-loaded nano-reservoirs in an experimental dry-eye mouse model. Physicochemical characterization confirmed the formation of a stable complex and the improved solubility of CsA. In vitro release and ex vivo permeation studies indicated a controlled drug release and improved permeation, respectively. Furthermore, tear volume measurement and corneal damage assessment using slit-lamp imaging suggested decreased dry eye symptoms, significantly increasing tear volume in the drug-loaded nano-reservoir-treated group. Moreover, histopathological studies corroborated the tear volume and slit-lamp imaging results, with reduced inflammation and neovascularization. The poorly water-soluble drug with cyclodextrin complex incorporated nanoreservoir films presents a potential alternative for managing various ocular diseases. Graphical Abstract

Novel Ketoconazole-Loaded Niosomal Gel with Carbamide for Enhanced Topical Delivery and Skin Hydration in Fungal Infections - Prajitha Biju; Manjunath M. Shenoy; Rouchelle Tellis; Ramesh Bhat; Ranajit Das; Ashwini Prabhu; Mohammed Gulzar Ahmed; Vivek Ghate (Journal of Pharmaceutical Innovation, 2025)

Human papillomavirus infection, cervical cancer and the less explored role of trace elements - Anne Boyina Sravani; Vivek Ghate; Shaila Lewis (Biological Trace Element Research, 2023)
Cervical cancer is an aggressive type of cancer affecting women worldwide. Many affected individuals rely on smear tests for the diagnosis, surgery, chemotherapy, or radiation for their treatment. However, due to a broad set of undesired results and side-effects associated with the existing protocols, the search for better diagnostic and therapeutic interventions is a never-ending pursuit. In the purview, the bio-concentration of trace elements (copper, selenium, zinc, iron, arsenic, manganese, and cadmium) is seen to fluctuate during the occurrence of cervical cancer and its progression from pre-cancerous to metastatic nature. Thus, during the occurrence of cervical cancer, the detection of trace elements and their supplementation will prove to be highly advantageous in developing diagnostic tools and therapeutics, respectively. This review provides a detailed overview of cervical cancer, its encouragement by human papillomavirus infections, the mechanism of pathology, and resistance. Majorly, the review emphasizes the less explored role of trace elements, their contribution to the growth and inhibition of cervical cancer. Numerous clinical trials have been listed, thereby providing a comprehensive reference to the exploration of trace elements in the management of cervical cancer.

A Sensitive Spectrofluorimetric Method for Curcumin Analysis - Anne Boyina Sravani; Elizabeth Mary Mathew; Vivek Ghate; Shaila A Lewis (Journal of Fluorescence, 2022)
Curcumin (CUR), a natural polyphenolic compound extracted from the rhizomes of Curcuma longa , is used as a pharmaceutical agent, spice in food, and as a dye. Currently, CUR is being investigated for cancer treatment in Phase-II clinical trials. CUR also possesses excellent activities like anti-inflammatory, anti-microbial, and anti-oxidant, therefore quality control is crucial. The present research work was to develop a new, simple, validated and time-saving rapid 96-well plate spectrofluorimetric method for the determination of CUR. The developed method was compared with routinely used high performance liquid chromatography (HPLC) technique. The developed method were found to be linear in the concentration range of 15 to 3900 ng/mL with R 2 ≥ 0.9983 for spectrofluorimetric and 50-7500 ng/mL with R 2 ≥ 0.9999 for HPLC method. Accuracy, intraday and interday precision was adequate, with RSD lower than the suggested limits. The limits for the detection and the quantification of CUR were 7 and 15 ng/mL for spectrofluorimetric, and 25 and 50 ng/mL for HPLC respectively. The Bland-Altman analysis demonstrated the similarities between the two methods. The 96-well plate method was successfully applied to determine CUR in solid lipid nanoparticles (SLNs) and chitosan nanoparticles (Chi-NPs). The developed spectrofluorimetric method can hence serve as a possible replacement for the HPLC method for the quantification of CUR in healthcare and food products.

Improved Oral Pharmacokinetics of Pentoxifylline with Palm Oil and Capmul® MCM Containing Self-Nano-Emulsifying Drug Delivery System - Ashay Manisha Shailendrakumar; Vivek M. Ghate; Manas Kinra; Shaila A. Lewis (AAPS PharmSciTech, 2020)

Development and Investigation of Vitamin C-Enriched Adapalene-Loaded Transfersome Gel: a Collegial Approach for the Treatment of Acne Vulgaris - Sandhya Vasanth; Akhilesh Dubey; Ravi G.S.; Shaila A. Lewis; Vivek M. Ghate; Sally A. El-Zahaby; Srinivas Hebbar (AAPS PharmSciTech, 2020)

Non-Propellant Foams of Green Nano-Silver and Sulfadiazine: Development and In Vivo Evaluation for Burn Wounds - Aleksandra Kurowska; Vivek Ghate; Arun Kodoth; Aarti Shah; Abhishek Shah; Badalamoole Vishalakshi; Bharathi Prakash; Shaila A. Lewis (Pharmaceutical Research, 2019)

Design of 2-Nitroimidazooxazine Derivatives as Deazaflavin-Dependent Nitroreductase (Ddn) Activators as Anti-Mycobacterial Agents Based on 3D QSAR, HQSAR, and Docking Study with In Silico Prediction of Activity and Toxicity - Nirzari Gupta; Vivek K. Vyas; Bhumika D. Patel; Manjunath Ghate (Interdisciplinary Sciences: Computational Life Sciences, 2019)

Development of MART for the Rapid Production of Nanostructured Lipid Carriers Loaded with All-Trans Retinoic Acid for Dermal Delivery - Vivek M. Ghate; Arun K. Kodoth; S. Raja; B. Vishalakshi; Shaila A. Lewis (AAPS PharmSciTech, 2019)

Generation of new leads as HIV-1 integrase inhibitors: 3D QSAR, docking and molecular dynamics simulation - Vivek K. Vyas; Shreya Shah; Manjunath Ghate (Medicinal Chemistry Research, 2017)

CoMFA and CoMSIA studies on 6,7-disubstituted-4-phenoxyquinoline derivatives as c-Met kinase inhibitors and anticancer agents - Palak Parikh; Manjunath Ghate; Vivek K. Vyas (Medicinal Chemistry Research, 2015)

3D QSAR study of 4H-chromen-1,2,3,4-tetrahydropyrimidine-5-carboxylate derivatives as potential anti-mycobacterial agents - Paresh Patel; Chetan Chintha; Manjunath Ghate; Hardik Bhatt; Vivek K. Vyas (Medicinal Chemistry Research, 2014)

Predictive 3D-QSAR and HQSAR model generation of isocitrate lyase (ICL) inhibitors by various alignment methods combined with docking study - Nirzari Gupta; Vivek K. Vyas; Bhumika Patel; Manjunath Ghate (Medicinal Chemistry Research, 2014)

Homology modeling, binding site identification, and docking study of human β-arrestin: an adaptor protein involved in apoptosis - Chetan Chintha; Nirzari Gupta; Manjunath Ghate; Vivek K. Vyas (Medicinal Chemistry Research, 2014)

Design of novel anaplastic lymphoma kinase (ALK) inhibitors based on predictive 3D QSAR models using different alignment strategies - Vivek K. Vyas; Ajay Patel; Nirzari Gupta; Manjunath Ghate (Medicinal Chemistry Research, 2014)

CoMFA and CoMSIA analysis of protein kinase B (PKBβ) inhibitors using various alignment methods - Vivek K. Vyas; Nirzari Gupta; Manjunath Ghate (Medicinal Chemistry Research, 2013)

3D QSAR studies on 5-(2-methylbenzimidazol-1-yl)-N-alkylthiophene-2-carboxamide derivatives as P. falciparum dihydroorotate dehydrogenase (PfDHODH) inhibitors - Vivek K. Vyas; Harshang Parikh; Manjunath Ghate (Medicinal Chemistry Research, 2013)

2D and 3D QSAR study on amino nicotinic acid and isonicotinic acid derivatives as potential inhibitors of dihydroorotate dehydrogenase (DHODH) - Vivek K. Vyas; Manjunath Ghate (Medicinal Chemistry Research, 2012)

QSAR modeling of some substituted alkylidenepyridazin-3-one as a non-cAMP-based antiplatelet agent - Vivek K. Vays; Anurekha Jain; Manjunath Ghate; Deepika Maliwal (Medicinal Chemistry Research, 2011)